Ni–Ti(–Cu) shape memory alloy interlayers supporting low friction functional coatings. (August 2015) - Callisti, M.; Danek, M.; Yasuda, K.; Evaristo, M.; Tichelaar, F.D.; Cavaleiro, A.; Polcar, T.
Abstract: The effects of Ni–Ti(–Cu) interlayers on the mechanical and tribological behaviour of W–S–C/Ni–Ti(–Cu) and W:DLC/Ni–Ti(–Cu) bilayer coatings have been investigated. The mechanical properties of the bilayers, measured at different depths by nanoindentation, exhibited a clear dependence on the combination between different Ni–Ti(–Cu) interlayers and top layers. The tribological performance of the bilayers was evaluated by pin-on-disk under different load conditions. The use of Ni–Ti(–Cu) interlayers improved the adhesion of the top layers and the resistance against surface damage such as delamination and cracking. Transmission electron microscopy analyses performed in the wear tracks of W–S–C/Ni–Ti and W:DLC/Ni–Ti bilayers tested with high load revealed that the formation of stabilised martensite was limited when a much harder top functional layer was employed. Highlights: Ni–Ti(–Cu) interlayers improve the adhesion of functional top layers. Ni–Ti(–Cu) interlayers enhance the crack resistance of hard coatings. Hard top layers limit the amount of stabilised martensite in Ni–Ti–Cu interlayers. Ni–Ti(–Cu) interlayers delay the tribolayer formation on W–S–C and W:DLC coatings.